Impact of Coolant Operation on Performance and Heterogeneities in Large Proton Exchange Membrane Fuel Cells: A Review - Marine Cornet; Erwan Tardy; Jean-Philippe Poirot-Crouvezier; Yann Bultel (Energies)
PEMFCs’ operation entails the presence of heterogeneities in the generation of current, heat and water along the active surface area. Indeed, PEMFCs are open systems, and as such, operating heterogeneities are inherent to their operation. A review of the literature reveals numerous attempts to achieve uniform current density distribution. These attempts are primarily focused on bipolar plate design and operating conditions, with the underlying assumption that uniform current density correlates with enhanced performance. Most studies focus on the influence of gas flow-field design and inlet hydrogen and air flow conditioning, and less attention has been paid to the coolant operating condition. However, uncontrolled temperature distribution over a large cell active surface area can lead to performance loss and localized degradations. On this latter point, we notice that studies to date have been confined to a narrow range of operating conditions. It appears that complementary durability studies are needed in order to obtain in-depth analyses of the coupled influence of temperature distribution and gas humidification in large PEMFCs.